Young, gifted and missing : the underrepresentation of African American males in science, technology, engineering and mathematics disciplines - Robins, Anthony G.; Knibbs, Locksley; Ingram, Ted N.; Weaver, Michael N., Jnr; Hilton, Adriel A. (Diversity in higher education ;, 2022)
Acting as a bridge between the academic and policymaking communities, Young, Gifted and Missing sets the stage for addressing critical issues around why African American men are absent in the STEM disciplines. The authors track the experiences of African American male students in STEM at every level of the educational system in order to produce successful models of achievement. The number of African American males who enroll in STEM degree programs as opposed to the lower numbers that ultimately graduate portends poorly for U.S. communities and democracy. The road to economic success and global participation requires a rich, educated community that must include African American males. There is a state of urgency to address this critical challenge. Action must happen now. An educated public, not just for some, but one for all is a must. Graduate students in STEM, education, and business disciplines, as well as executive leadership in education, corporate and non-profit entities stand to benefit from reading this volume. Lastly, those looking to research the successes of African American males in STEM disciplines would find this book purposeful.